Geomorphological Study for Selective Sections of Injana Formation/ Northern Iraq - Yasser Mahmood Jadalah; Ameera Asmayll Heissan; Sawsan Hameed Al-Hazaa (Tikrit Journal of Pure Science, 2023)
The research includes a geomorphological research of Injana Formation for three sections Hemreen/Tikrit, Hemreen/Tozkormato and Kany Domelan (Dibs). The study includes the analysis of this geomorphological map results in limitating four geomorphological units of Homoclinal origin and three units of erosional origin and surface drainage . It has  been shown from the  analysis of the surface drainage net that the  drainage pattern is the dominate in the study areas